Agenda
039-0038-001 BASQUE CHILDREN'S COMMITTEE Committee Meeting to be held at 5 p.m., Wednesday, April 6th, 1938, in the House of Commons, S.W. AGENDA 1. Apologies for Absence. 2. Reports on - (a) Basque Children's Trust. (b) Administration Sub-Committee . (c) Conference, Saturday, April 9th. (d) Concert (e) Roman Catholic Sub-Committee. 3. Financial Position. Renewal of Insurance 4. Centres business (a) Future of - i. Brixton. No. of Children ... 81 ii. Margate (Eastcliff House) :: ... 62 iii. North Oxon. (Witney) :: ... 24 iv. Middlesbrough :: ... 14 v. Brighton :: ... 30 vi. Swansea : : ... 29 vii Blackboys :: ... 11 viii. High Wycombe :: ... 21 ix, Leeds : : ... 21 x. Tynemouth ... :: ... 17 xi. Offenham (Birmingham) :: ... 35 Roman Catholic Homes i. Littlehampton :: ... 11 ii. Holly Mount, Bury. :: ... 11 (b) Death of Jose Sobrino, (Faringdon) :: :: Inaki Zubizarreta Larranaga (Scarborough) (c) Report on negotiations with Home Office re children in private homes ... Sheffield. 5. Report on Repatriation 6. Resignation of Mrs. Reynolds. 7. Date of next meeting. 8. Any other business. 292/946/39/38